Employing the Physicochemical, Spectroscopy, Antimicrobial and Antifungal Efficacy Studies of P-Hydroxy Acetophenone Based Azo Schiff Base Complexes - Wurood Ali Jaafar (Journal of Global Pharma Technology, 2018)
The azo Schiff base [Reaction of 4-aminoanypyrine and P-hydroxy acetophenone] and O-Phenylene diamine have been prepared. One azo  Schiff  base  chelate  of Co(Il), Ni(II), Cu(II) and Zn(II)ion was also  prepared. The chemical frameworks of the azo Schiff base and   like elemental analyses (CHN), determinations of molar conductance, 1 H &13C NMR, IR mass and electronic spectroscopy .The elemental analyses exhibited the combination of [L: M] 1:1 ratio. Established on the values IR spectral, it is showed that the azo Schiff base compound acts as neutral hexadentate ligand bonded with the metal ion from two hydroxyl, two azomethine  and  two azo groups  of the  azo  Schiff  base  compound  in  chelation  was confirmed  by  IR  , 1Hand 13CNMR  spectral outcomes. The UV-Vis spectral values appeared the existence of π→π* (phenyl ring), n→π* (N=N, -OH and HC=N) and an octahedral structure was suggested for the coordinate. The mass spectral outcomes assured the purity of the ligand. Furthermore, the antimicrobial and antifungal efficacy results revealed that the metal complexes were found to be more active than the free ligand.  In general the activity order of the synthesized compounds can be represented as Fe (II) > Cu (II) > Ni (II) > Zn (II) > Co (II) > L.   Keywords: Azo Schiff base, P-hydroxy acetophenone, antifungal efficacy, Spectroscopy.